DEVELOPMENT IN THE USE OF COCONUT FARM RESIDUES FOR THE MANUFACTURE OF COIR-WOOD-CEMENT AS ALTERNATIVE CONSTRUCTION MATERIAL - R. N. Palomar; L. J. Penamora; N. J. Melencion (International Coconut Community Journal, 2000)
A new product using farm wastes from coconut plantation is being developed as an alternative building material. The product, coir-wood-cement board (CWCB), is made from husk fiber of coir and shredded sapling or excelsior that are mixed separately with cement at a predetermined ratio of 70% cement to 15% coir excelsior by weight basis. Mixture of saturated coir/excelsior and cement is mat-formed and pressed to the desired thickness and then conditioned by air-drying to produce CWCB. Its dimension is 61 cm wide and 244 cm long with thickness ranging from 8 mm to 25 mm CWCB meets the strength requirements set by PHILSA standard specification for particleboard (PHILSA 106, 1975). It is being service-tested as an alternative material for expensive construction materials such as plywood, particleboard and cement hollow blocks. It has been found suitable for such uses as exterior/interior walls, partition panel and ceiling of building as well as furniture components such as table top and cabinet siding. Production of CWCB needs the major equipment/machinery such as decorticating machine, shredding machine, blending machine, hydraulic press, trimmer and lifter. Except for lifter, these machines can be designed and fabricated locally. Estimated total investment cost of PhP 3.76 million is needed to establish a CWCB plant that includes equipment, land rental, building and working capital. About 37,500 boards can be produced every year with internal rate of return of 35.20% and payback period of 2.68 years.